Clinical Profile of HLA-B27-Associated Uveitis in an Egyptian Cohort - Abd El Latif, Eiman (Clin Ophthalmol, 2020)
PURPOSE: To describe the clinical profile of patients with HLA-B27-associated uveitis at 2 Egyptian tertiary eye centers. METHODS: A retrospective study reviewing the medical records of all patients with HLA-B27-associated uveitis served at 2 uveitis referral clinics in Egypt between January 2010 and June 2018. RESULTS: The study included a total of 554 patients. Anterior uveitis was the most common type. Ankylosing spondylitis was an important systemic comorbidity in the present study, affecting 27.4% of our patients. Cataract was the most frequent ocular complication. By the conclusion of the study, 6.1% of the affected eyes had a BSCVA poorer than 20/200. CONCLUSION: The clinical profile of HLA-B27-associated uveitis in our cohort of Egyptian patients is similar to that reported from other regions of the world. In our study, a relatively high rate of cataract was observed.